Business intelligence and agile methodologies for knowledge-based organizations : cross-disciplinary applications - El Sheikh, Asim Abdel Rahman; Alnoukari, Mouhib, 1965- (Hershey, PA : Business Science Reference, 2012)
'This book highlights the marriage between business intelligence and knowledge management through the use of agile methodologies, offering perspectives on the integration between process modeling, agile methodologies, business intelligence, knowledge management, and strategic management'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Business intelligence; Knowledge management